Pro SQL Server 2005 Integration Services - Wightman, James; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
SQL Server Integration Services is groundbreaking. It exists for both the database administrator and the developer, as well as that new role SSIS has created between the two—the data artisan. Pro SQL Server 2005 Integration Services contains everything you could ever hope to know about this exciting development from Microsoft: developer insight, Microsoft group manager–level access, personal experience of using the technology in the real–world, and fine–grained analysis. If you want to rapidly gain knowledge and context from your data, Microsoft's latest and greatest interpretation of enterprise application integration, SQL Server Integration Services, is for you. As part of the extensive SQL Server suite, Integration Services is a more serious and expandable interpretation of the integration paradigm than previously available. At once both simple to use yet incredibly complex, it goes far beyond being a reimagining and reengineering of DTS, and it's all presented in a familiar Visual Studio context. It's agile, it's service-oriented, it's everything to everyone. Written for the developer, the database administrator, and the data artisan, Pro SQL Server 2005 Integration Services will show you how to develop and deploy enterprise SSIS solutions in multibillion–item environments. It's everything SSIS, explained for everyone!
Introducing SQL Server 2005 Integration Services -- The Architecture of SSIS -- From DTS to SSIS -- The IDE and Extending Visual Studio -- Package Hierarchy -- Control Flow -- Maintenance Plans -- Data Flow Data Sources -- Basic Data Flow Transformations -- Advanced Data Flow Transformations -- Data Flow Destinations -- Optimization for SSIS -- SSIS Security -- Scripting, .NET Style -- Custom Components.
Keywords: Database management; Software engineering; Database Management; Software Engineering/Programming and Operating Systems